Caracterização hidrogeoquímica do reservatório da Usina Hidrelétrica de Coaracy Nunes-Amapá - BEZERRA, Clauber dos Santos (Universidade Federal do Pará, 2019)
This study characterized chemically the water of the reservoir of the hydroelectric power plant of Coaracy Nunes, located in the Amapá state, about 20 km from the city Ferreira Gomes and 150 km from the city of Macapa. Samples were collected in four quarterly campaigns during the year, in the period October 2008 to September 2009, the study aimed to characterize the spatial and seasonal behavior of chemical parameters, and physicalchemicalsof the water in thereservoir of the hydroelectric power plant of Coaracy Nunes. In the Amapá state, the predominant climate is equatorial, in the months of the campaigns, from December to May was the period with the high estrate of rainfalls, and the months of lowest rainfalls was understood from August to November. In the total 13 point were sampled in each campaign, distributed upstream of the reservoir in order to represent all environments of the reservoir. At each point, samples were collected from water at four depths (surface, double the secchi, middle and bottom). In the collected samples were measured physicochemical parameters such as pH, temperature, conductivity, ammonium ion, STS, HCO3-, hardness and OD. The chemical elements(Al, As, Ba, Be, Ca, Cd, Co, Cr, Cu, Fe, Ga, Hg, K, Li, Mg, Mn, Na, Ni, Pb, Se, Sr, V, Zn) were analyzed by mass spectrometry of a source for inductively coupled argon plasma. (ICP-MS). In preliminary assessments none showed evidence stratification in the reservoir. The concentrations of aluminum,iron and manganese are highlighted within this context, and have high concentrations, once compared with the chemical characteristicsofwatersofthe Amazon region. The reservoir had the following chemical and physical-chemical particulars average values obtained during dry periods in (μg/L) : Al (487,44), Ca (604,12), Fe (458,78), K (798,05), Mg (625,40), Mn (123,42), Na (1903,719), Pb (3,86), pH (6,50), Cond. (μs/cm) (33,20), temperature ºC (27,1), hardness mg/L (6,09), HCO3 -(9,00). The reservoir of Coaracy Nunes presented a tendency to stratification in the deepest collection stations indicated by the points MCN 02, MCN 03 e MCN 04, in other points this trend is less marked, because the other points have less depth. Throughout the longitudinal axis of the reservoir we did not observe any tendency of the reservoiractasaretention systemofsubstancein relationtothat flock toit. Sampling points in greater depth, the reservoir has decreased the concentration of dissolved oxygen with increasing depth,creating anoxic zones in the reservoir bottom, favoring the release of chemical elements as Fe and Al which are incorporated to the particles in suspension, through the anaerobic processes.